2008
DOI: 10.1038/jid.2008.103
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Polyphenol Epigallocatechin-3-Gallate Suppresses Collagen Production and Proliferation in Keloid Fibroblasts via Inhibition of the STAT3-Signaling Pathway

Abstract: Keloids are benign skin tumors characterized by collagen accumulation and hyperproliferation of fibroblasts. To find an effective therapy for keloids, we explored the pharmacological potential of (-)-epigallocatechin-3-gallate (EGCG), a widely investigated tumor-preventive agent. When applied to normal and keloid fibroblasts (KFs) in vitro, proliferation and migration of KFs were more strongly suppressed by EGCG than normal fibroblast proliferation and migration (IC(50): 54.4 microM (keloid fibroblast (KF)) ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
98
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 47 publications
11
98
0
1
Order By: Relevance
“…This is in agreement with data published by Park et al 32 who reported that EGCG inhibited proliferation and migration of keloid and to lesser extent normal fibroblasts in vitro. We also demonstrated that at higher doses of EGCG (100 µg/ml and above) treated fibroblasts demonstrate a statistically significant (P<0.05) increase in the quantity of cells in G 0 /G 1 compared to controls indicating that a smaller fraction of cells were dividing.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This is in agreement with data published by Park et al 32 who reported that EGCG inhibited proliferation and migration of keloid and to lesser extent normal fibroblasts in vitro. We also demonstrated that at higher doses of EGCG (100 µg/ml and above) treated fibroblasts demonstrate a statistically significant (P<0.05) increase in the quantity of cells in G 0 /G 1 compared to controls indicating that a smaller fraction of cells were dividing.…”
Section: Discussionsupporting
confidence: 83%
“…13, [32][33][34] Furthermore, microorganisms with resistance to systemic antibiotics have increased resistance to many topical antimicrobial treatments currently in use. 35 There is a need to evaluate the efficacy of topical agents that can be used to supplement or enhance current systemic antimicrobial therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, STAT3 triggers a transduction signal that is required for the synthesis of the extracellular matrix and cellular proliferation of fibroblasts isolated from hypertrophic scars (36). In keloids, a fibrotic disease, STAT3 promotes collagen synthesis, proliferation, and migration of fibroblasts (37,38). Moreover, an aberrant activation of this pathway has also been reported in human sclerodermic skin and in a mouse model of SSc induced by bleomycin (19).…”
Section: Discussionmentioning
confidence: 99%
“…3 The lack of an animal model that can truly mimic human KD in vivo condition imposes limitations when investigating functional activities of potential therapeutic agents in treating KD. 4,5 However, these models have failed to provide the essential components of skin tissue that occur in vivo, such as mature ECM, blood vessels, inflammatory cells, and intrinsic and extrinsic biochemical interactions. Therefore, the ultimate aim of this study was to determine the applicability of recent research findings in existing in vitro keloid models to our recently developed keloid organ culture (OC) model.…”
mentioning
confidence: 99%